2021
DOI: 10.33448/rsd-v10i11.19846
|View full text |Cite
|
Sign up to set email alerts
|

Levantamento de imaturos de libélulas (INSECTA: ODONATA) em tanques escavados de piscicultura na mesorregião de Alfenas-MG

Abstract: Imaturos de libélula são encontrados em uma vasta quantidade de ambientes aquáticos de água doce, dentre eles, os tanques escavados para piscicultura. Como são predadores durante a fase aquática, acabam por causar grandes prejuízos nas fases iniciais de produção da aquicultura de água doce. No entanto, os estudos de quais são as libélulas mais comuns em tanques de piscicultura ainda são escassos no Brasil, sendo que este é primeiro passo para se pensar num controle eficaz. Por esse motivo, coletamos imaturos d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The selection of the Odonata genera used in the experiments was based on the results of studies of Fortunato et al, 2021 with a survey of the genera in five excavated fish farming ponds at the Universidade Professor Edson Antônio Velano between October 2018 and March 2019. In this survey 692 larvae were collected, being 34.41% of them represented by the Miathyria genus and 20.4% by the Erythemis genus.…”
Section: Selection Of Odonata Generamentioning
confidence: 99%
See 1 more Smart Citation
“…The selection of the Odonata genera used in the experiments was based on the results of studies of Fortunato et al, 2021 with a survey of the genera in five excavated fish farming ponds at the Universidade Professor Edson Antônio Velano between October 2018 and March 2019. In this survey 692 larvae were collected, being 34.41% of them represented by the Miathyria genus and 20.4% by the Erythemis genus.…”
Section: Selection Of Odonata Generamentioning
confidence: 99%
“…However, despite their ecological importance in aquatic communities, when referring to fish farming environments, specifically in excavated ponds and in the initial moments of fish life, these insects can cause great productive losses as mentioned above (Tave, Rezk, & Smitherman, 1990). According to studies by Santos, Costa, and Luz (1988), De Marco Junior, Latini, and Reis (1999), Fonseca, Sanches, Fonseca, Quintilhiano, and Silva (2004), and Fortunato et al (2021, among the main genus of Odonata found in fish farms, Pantala Hagen, 1861, Orthemis Hagen, 1861, Miathyria Kirby, 1889, Erythrodiplax Brauer, 1868, Erythemis Hagen, 1861 belong to the Libellulidae family.…”
Section: Introductionmentioning
confidence: 99%